Are There Differences in “Intelligence” Between Nonhuman Species? The Role of Contextual Variables - Colombo, Michael; Scarf, Damian (Frontiers in Psychology, 2020)
We review evidence for Macphail’s (1982, 1985, 1987)Null Hypothesis, that nonhumans animals do not differ either qualitatively or quantitatively in their cognitive capacities. Our review supports the Null Hypothesis in so much as there are no qualitative differences among nonhuman vertebrate animals, and any observed differences along the qualitative dimension can be attributed to failures to account for contextual variables. We argue species do differ quantitatively, however, and that the main difference in “intelligence” among animals lies in the degree to which one must account for contextual variables.